Electromagnetics of time varying complex media : frequency and polarization transformer - Kalluri, Dikshitulu K. (Taylor & Francis, 2010)
Completely updated and revised to reflect recent advances in materials science and electromagnetics, Electromagnetics of Time Varying Complex Media: Frequency and Polarization Transformer, Second Edition provides a comprehensive e-amination of current topics of interest in the research community--including theory, numerical simulation, application, and experimental work. Written by a world leader in the research of frequency transformation in a time-varying magnetoplasma medium, this new edition of a bestseller discusses how to apply a time-varying medium to design a frequency and polarizatio.